Postpartum hemorrhage: clinical features and management in a tertiary care center of Nepal - Pradhan Malla, Anagha; Acharya, Swikrity; Thapa, Bijay (Journal of Patan Academy of Health Sciences, 2023)
Introduction: Obstetric haemorrhage continues to account for a substantial proportion of maternal deaths in Nepal, despite implementation of different strategies. The most common type of obstetric haemorrhage is postpartum hemorrhage (PPH), mainly primary. Understanding its burden in the health care setting was the objective of this study by assessing its prevalence, associated factors and management. Method: This was a retrospective study conducted at Patan Academy of Health Sciences from Mar 2019 to Mar 2022. Demographic, obstetrical, medical factors and management of primary PPH was collected from medical record. Statistical analysis was done using Statistical Packages for Social Sciences (SPSS-20). Results were expressed using frequencies, tables and figures. Result: From a total 17,770 deliveries, primary PPH was seen in 84(0.47%). Most of them 49(58.3%) were multipara. The frequency and impact of PPH can be effectively reduced by reducing avoidable risk factors, especially those related to obstetric interventions as increased caesarean section rate which was 48(57.1%) among primary PPH. Other associated risk factors were induction of labor 32(38.1%), pre-existing medical diseases 32(38.1%), history of antepartum hemorrhage 15(17.9%), previous caesarean section 19(22.6%). Uterine atony 43(51.2%), abnormal placentation disorder 16(19%), genital trauma 9(10.71%), retained tissue 5(5.95%) were the leading causes of PPH. PPH in morbidly adherent placenta like placenta accreta spectrum was 8(9.5%) and placenta increta 1(1.2%). PPH was controlled by conservative management in 24(28.6%). Surgical intervention was required in 34(40.5%) including hysterectomy in 14(16.7%). Conclusion: PPH can be minimized by extra vigilance and planned conjoined management.